THE EMPOWERMENT OF CHILDREN IN EDITH NESBIT’S THE RAILWAY CHILDREN - Adam Anshori (University of Kuningan, 2016)
This research is aimed at describing the empowerment of children in Edith Nesbit’s The Railway Children. The problems formulated in the research will be answered in the descriptions consisting of thoughts, actions, and feelings of the main characters in the novel and presenting other characters’ comments dedicated to the main characters. The main source of the research data was Edith Nesbit’s The Railway Children. It is considered as a children’s literature. The focus of the research was events in the novel which showing the empowerment of the main characters. The data consist of thoughts, actions, and feelings of the main characters and presenting other characters’ admirable comments dedicated to the main characters. The data were analyzed inductively by using qualitative content analysis. The instrument of the research was the researcher himself. To get trustworthiness of the data, the researcher used four criteria, namely: credibility, transferability, dependability, and confirmability. The findings of the research showed that the novel contains of children’s empowerment, which can be divided into three categories. They are Thought Empowerment, Action Empowerment and Feeling Empowerment. As empowerment of children is considered as an important aspect in children’s story and it has great influence to enrich children’s intelligence and emotion in their growing period, The Railway Children can be categorized as a good novel. Keywords: children’s literature, children’s empowerment